Molecular Markers Distinguishing T Cell Subtypes With TSDR Strand-Bias Methylation - Minskaia, Ekaterina; Saraiva, Barbara C.; Soares, Maria M. V.; Azevedo, Rita I.; Ribeiro, Ruy M.; Kumar, Saumya D.; Vieira, Ana I. S.; Lacerda, João F. (Frontiers in Immunology, 2018)
Human regulatory CD4+CD25+FOXP3+ T cells (Treg) play important roles in the maintenance of self-tolerance and immune homeostasis in various disease settings and are also involved in the suppression of effective immune responses. These cells are heterogeneous in phenotype and function, and the ability to reliably distinguish between various FOXP3-expressing subpopulations can affect the development of successful therapies. This study demonstrates that hypomethylated CpG sites, present in four regions of the FOXP3 locus, CAMTA1 and FUT7 gene regions, can be used to distinguish several subsets of Treg from conventional CD4+ T lymphocytes (Tcon) in donors of both genders. We describe a previously unreported strand-bias hemimethylation pattern in FOXP3 promoter and TSDR in donors of both genders, with the coding strand being demethylated within promoter and methylated within TSDR in all CD4+ lymphocyte subtypes, whereas the template strand follows the previously described pattern of methylation with both regions being more demethylated in Treg subtypes and mostly methylated in Tcon. This strand-specific approach within the TSDR may prove to be instrumental in correctly defining Treg subsets in health and in disease.